ICORG-92 remote sensing applications and geographic information systems recent trends - Muralikrishna, I. V.; Jawaharlal Nehru Technological University; ICORG-92 Hyderabad, India) (1992. (New Delhi Tata McGraw-Hill, 1992)
Seminar papers; chiefly in the Indian context.
Cover title: Remote sensing applications and geographic information systems.
Keywords: Remote sensing -- Congresses; Geographic information systems -- Congresses